EFFECT OF SOLE AND COMBINED INOCULATION OF RALSTONIA SOLANACEARUM AND MELOIDOGYNE JAVANICA ON TOMATO - P. P. GHOSH,; S. DUTTA, (The Bioscan, 2014)
The effects of Meloidogyne javanica alone and in different combination with Ralstonia solanacearum on tomato were investigated. The highest shoot length reduction (32.1%) was at the highest density of both the parasites over control. The highest initial population density of M. javanica was solely responsible for the highest root length reduction (33.25%) and shoot dry weight reduction (67.44%). The highest density of R. solanacearum is solely responsible for root fresh weight reduction (22.28-30.85%) irrespective of M. javanica densities. Higher density of M. javanica produced higher root fresh weight (1.69 - 1.96 g) in the absence of R. solanacearum over control (1.75 g). The gall intensity was dose dependent in absence of R. solanacearum. However, in the presence of R. solanacearum at its higher density, M. javanica produced lowest number of galls (20.9-34.7). The synergistic effects on percent wilt incidences (52 - 95%) were more prominent at lower levels of R. solanacearum population with pathogenic levels of M. javanica. Conclusively, the role of M. javanica is synergistic only if the density of R. solanacearum is lower than 105 cfug-1 soil, however, higher R. solanacearum population (107-109 cfug-1 soil) drastically inhibits the activity of root-knot nematode in the rhizosphere.